Relaxamento progressivo, stress, enfrentamento e qualidade de vida em pessoas com apneia obstrutiva do sono - Mellado, Cristiane Regina dos Santos Barros [UNESP] (2015)
The progressive relaxation of Jacobson, a technique that seeks to minimize the effect of stress through exercise muscle stiffness and relaxation to apply in behavioral therapy for the treatmento of psychological aspects related to syndrome of Obstructive Sleep Apnea or OSA. The syndrome characterized by the occurence of repetitive events for complete or partial obstruction of the upper airway during sleep. Affects the stress, state that impairs the body's homeostasis, in coping strategies or adaptative responses to stressful situations, and also the quality of life (QOL), individual's perception of this life in accordance with their system of values and culture. Thus, the study sought to evaluate the effect of progressive relaxation on stress and quality of life in people with OSA identify coping strategies reported by the participants before and after the intervention. For this intervention research was conducted with 57 individuals between 24 and 72 years, 32 (56.1%) males and 25 (43,8%) were female. Of these, 44 (77.1%) live in stable relationships and 47 (82.4%) with children. As for education, 32 (56.1%) had a college degree, with five graduate and quite varied professions with higher incidence of retirees, banking, lawyers, contract managers, credit stoves, researchers and home. The assessment instruments used were the Inventory of Stress Symptoms in Adults Lipp, Coping Inventory of Folkman and Lazarus Strategies and WHOQOL-bref the World Health Organization Quality of Life Group. The participants were divided into two groups, G1 being the intervention group with progressive relaxation and G2 control group. The results we received quality and quality treatment showed that 68.4% of participants had stress being, 48.7% in G1 and 51.2% in G2. After, the intervention the symptoms of stress detect in 36.8% of participants in the intervention group (G1) and 56.4% in the control group (G2). The Coping Strategies commonly used before the...